KOMUNIKASI PERSUASIF TERAPIS RUMAH SAKIT JIWA TAMPAN DALAM PROSES REHABILITASI PASIEN NARKOBA - Fanggini, Randy; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Nowadays, there are a lot of people who fell into the dark side of the world, drugs. There are a lot of people who started using drugs. This is such a bad phenomenon that happened in the society, especially in teenagers. This problem has affected all the activities. Using drugs is a big problem as well as fighting among people with no reason, free sex, etc. But using drugs is one of most big topics that people always talk about. In this problem, the drug addicts came from any kind of economic level. Not only wealthy people, but poor people also did this. Fortunately, In Pekanbaru, there is a place for those people who want to start a new life, a place for rehabilitation, which called Mental Hospital Tampan. But, we can still find some minus from this program. Mental Hospital Tampan still needs more psychologist to participate on this program. Psychologist, a person who can talk to the drug addicts in distinctive way, and in a distinctive room. So the drug addicts can talk about their personality without being scared of people would listen to their problems. By doing this program, we found that the number of people doing drugs decreases. This program really helpful for people in Pekanbaru. This research aims to know all the strategies that the psychologist has been using, how the psychologist talk to the drug addicts, when does the psychologist tell all the important things to the drug addicts, and what is the effect of doing this program.This research uses qualitative method, where all the data has been gotten from observation, interview, and documentation. There are 5 informant, which consist of (drug agency managers, head of the rehabilitation unit, administrator, counselor, and resident). Analytical data techniques that has been using in this research is Milles and Huberman techniques.The result of the research showed that persuasive communication in Mental Hospital Tampan has been applied some methods. One of the methods is approaching the drug addicts and giving them some motivation as well as advices that affect to their way of thinking. So they can think clearly and think about positive things. The other methods is very unique. The psychologist hand the information by movies that motivating the drug addicts, not by any electronic devices. The time the psychologist delivers the information is depends on the time that the psychologist and the resident has been determined before. The biggest aim of this program is to change the way drug addicts think and to change their attitude to a better one.Keyword :Persuasive Communication, Rehabilitation, Drug